PENINGKATAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) SISWA KELAS IV SDN 008 RAMBAH - Asmayulis Asmayulis (STKIP ROKANIA, 2018)
This study aims to improve the learning outcomes of IPS students of fourth grade SD Negeri 008 Rambah by applying Cooperative Learning Model Numbered Heads Together (NHT). This type of research is a Classroom Action Research (PTK) conducted in two cycles. The subject of this research is the fourth grader of SD Negeri 008 Rambah which amounted to 32 students. The data obtained in the study are the results of student learning obtained through Daily Deuteronomy at the end of the cycle, teacher activity obtained from the teacher activity observation sheet, student activity obtained through student activity observation sheet. Analysis of student learning outcomes on the average score of 60.78 and 35.5% classical learning completeness, the average Cycle I 77.5 experienced an increase of 18.09% and classical completeness 71.88%, and cycle II average 83.28 years experienced an increase of 37.02% and 87.5% classical thoroughness.